Pengaruh Model Kooperatif Tipe Scramble Terhadap Hasil Belajar Peserta Didik Pada Tema 7 Indahnya Keragaman Di Negeriku Subtema 2 Di Kelas IV SDN 71 Banda Aceh - Cut Rania Kirana; M. Husin; Alfiati Syafrina (Jurnal Ilmiah Mahasiswa Pendidikan Guru Sekolah Dasar, 2022)
This study aims to see the significant impact of using the scramble-type cooperative model on students’ learning achievement in Theme 7 The Beauty of Diversity in my Country, Sub-theme 2, especially in social studies subjects regarding the diversity of traditional houses and traditional clothing in Indonesia. The research method used is a quantitative approach of the Pre-Experimental type with the One Group Pretest-Posttest design. This research was carried out at the 71 Banda Aceh State Elementary School on Jalan Mesjid Al-Qurban, Mibo Village, Banda Raya District, Banda Aceh City. Sampling using saturated sampling technique, the sample used is all students in fourth grade totaling 26 people. The data collection technique used tests in the form of multiple choice pretest and posttest, totaling 20 questions. The data analysis technique used hypothesis testing with t-test statistics at a significant level α = 0.05. The results of the t-test hypothesis research obtained tcount of 15.04 table of 1.71 so that H0 is rejected and H1 is accepted. Thus, it can be concluded that there is a significant impact in the use of the scramble type cooperative model on student learning achievement in Theme 7 The Beauty of Diversity in My Country, Sub-theme 2 in grade IV SDN 71 Banda Aceh.